Seasonal distribution of salts in the plant organs of Vitis Vinifera L. (cv. Colombar) irrigated with saline water - Van Zyl, Elmarie (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1997.